1984
DOI: 10.1007/bf00495414
|View full text |Cite
|
Sign up to set email alerts
|

On the topology of the catalase biosynthesis and-degradation in the guinea pig liver

Abstract: The biosynthesis, transport and degradation of catalase have been studied in the guinea pig liver parenchymal cell using 2-allyl-2-isopropylacetamide (AIA) as an inhibitor of de novo formation of catalase. Total catalase activity was assayed biochemically; cytoplasmic catalase was measured microspectrophotometrically after quantitative diaminobenzidine staining of the liver. By morphometry, number and size of peroxisomes in catalase stained sections were determined. From our data we conclude that (1) the final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Catalase was initially thought to primarily be a peroxisomal protein, but subsequent studies indicated a significant cytosolic pool as well (11,43-46). A number of studies have focused on understanding catalase maturation with respect to its sub-cellular compartmentalization.…”
Section: Discussionmentioning
confidence: 99%
“…Catalase was initially thought to primarily be a peroxisomal protein, but subsequent studies indicated a significant cytosolic pool as well (11,43-46). A number of studies have focused on understanding catalase maturation with respect to its sub-cellular compartmentalization.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that densitometric analysis of immunostained light microscopic sections could provide similar information as the more elaborate and timeconsuming quantitative immunoelectron microscopy. Indeed, densitometry has been used for detection of catalase concentration in DAB-stained light microscopic sections (Geerts and Roels, 1981;Geerts et al, 1984;Kerckaert et al, 1989). The immunohistochemistry, however, is more versatile because it can be used for the investigation of a larger number of enzyme proteins against which an antibody is available.…”
Section: Effect Of Bezafibrate Treatment On Labeling Density Of Peroxmentioning
confidence: 99%
“…However, there is also the possibility that the turnover of catalase is increased while synthesis remains unaffected. In the liver, the half-life of catalase is species-dependent and varies from 1.5 to 5 days (Price et al 1962;Jones and Masters 1976;Geerts et al 1984). Degradation of peroxisomes in toto via autophagocytosis was not observed, and inhibition of the enzyme can be ruled out because the antigen is equally disappearing, as detected by the decreasing ␣-catalase immunofluorescence signal.…”
Section: Discussionmentioning
confidence: 98%
“…Granulosa sheets were rinsed twice in homogenization buffer [imidazol-HCl 0.01 M, pH 7.2, containing sucrose (8.5%), EDTA (1 mM), and ethanol (22 mM)] (Geerts et al 1984). Sheets were resuspended in 500-1000 l homogenization buffer and disrupted by sonication (six times for 15 sec) on ice using a Vibracell VC-130 sonicator resulting in an output of 4 W. Protein concentrations were measured according to Bradford (1976) using the BioRad (Hercules, CA) protein assay kit.…”
Section: Staining Of Peroxisomesmentioning
confidence: 99%